Metabolic and bariatric surgery: Selection and preoperative work-up - Smit, J G M; Lubbe, J; Murphy, A; Mawson, K; Koto, M Z; Conradie-Smit, M; May, W (South African medical journal, 2025)
RECOMMENDATIONS 1. We suggest that a comprehensive medical and nutritional evaluation be completed and nutrient deficiencies corrected in candidates for MBS (Level 4, Grade D). 2. We suggest screening for and treatment of obstructive sleep apnoea in people seeking MBS (Level 4, Grade D). 3. Preoperative smoking cessation can minimise postoperative complications (Level 2a, Grade B).